Burns objective scar scale (BOSS): Validation of an objective measurement devices based burn scar scale panel. Issue 1 (February 2020) - Lee, K.C.; Bamford, A.; Gardiner, F.; Agovino, A.; ter Horst, B.; Bishop, J.; Grover, L.; Logan, A.; Moiemen, N.
Highlights: Combined Dermascan and Cutometer can be used to accurately to differentiate a hypertrophic scar from normal scar or normal skin. Colour related parameters were found to be inaccurate to differentiate a hypertrophic scar from normal scar or normal skin. An global objective scar assessment panel is presented, but requires further validation in a different cohort of patients. Abstract: Aims: Hypertrophic scars in burn survivors are a major cause of morbidity but the development of evidence based treatments is hampered by the lack of objective measurements of these scars. The objective of our study is to investigate the most accurate parameters for objective scar assessment and to create a combination score to facilitate the use of a panel of objective scar measurement tools. Methods: Three independent assessors evaluated fifty five scar sites on fifty five burn patients with both the subjective modified Vancouver Scar Scale (mVSS) and a panel of objective measurement tools including the DSM II Colormeter, Cutometer, Dermascan high frequency ultrasound. The sensitivity and specificity of the objective scar parameters in predicting a mVSS score of 6 or more using the Receiving Operator Characteristic Area under the curve (ROC AUC) was then calculated and the most accurate parameters were combined to create an objective global scar score. Results: The ROC AUC values were found to be highest for the Dermascan scar thickness (0.897), dermal intensity and intensity ratio (0.914 and 0.919), Cutometer R0 value (0.942), and R0 ratio (0.944). For colour measurements, ratios of scar to normal skin performed better than the single parameters for both erythema and pigmentation measurements: DSM II Erythema ratio vs Erythema (0.885 vs 0.818), DSM II a* ratio vs a* (0.848 vs 0.741); DSM II Melanin ratio vs Melanin (0.854 vs 0.761), DSM II L* ratio vs L* (0.862 vs 0.767). Analysis of the ROC AUC with chi-square test values showed that the highest AUC (0.786) was obtained with the combination of the Cutometer R0, Dermascan scar thickness, intensity and their respective scar to normal skin ratios. A total score of 5 and above (out of 6 parameters) had the highest combined sensitivity (69.0%) and specificity (83.3%). Conclusion: The objective parameters for the DSM II Colormeter, Cutometer and Dermascan high frequency ultrasound were all found to have moderate to strong ROC AUC values and combination of the Cutometer R0 and Dermascan scar thickness and intensity values can be used to create an objective global scar scale that can accurately differentiate patients with hypertrophic burn scarring from non-hypertrophic scars or normal skin.